Responses of nectar‐feeding birds to floral resources at multiple spatial scales. Issue 7 (22nd September 2015) - Schmid, B.; Nottebrock, H.; Esler, K. J.; Pagel, J.; Pauw, A.; Böhning‐Gaese, K.; Schurr, F. M.; Schleuning, M.
Abstract : The responses of animal pollinators to the spatially heterogeneous distribution of floral resources are important for plant reproduction, especially in species‐rich plant communities. We explore how responses of pollinators to floral resources varied across multiple spatial scales and studied the responses of two nectarivorous bird species (Cape sugarbird Promerops cafer, orange‐breasted sunbird Anthobaphes violacea ) to resource distributions provided by communities of co‐flowering Protea species (Proteaceae) in South African fynbos. We used highly resolved maps of about 125 000 Protea plants at 27 sites and estimated the seasonal dynamics of standing crop of nectar sugar for each plant to describe the spatiotemporal distribution of floral resources. We recorded avian population sizes and the rates of bird visits to > 1300 focal plants to assess the responses of nectarivorous birds to floral resources at different spatial scales. The population sizes of the two bird species responded positively to the amount of sugar resources at the site scale. Within sites, the effects of floral resources on pollinator visits to plants varied across scales and depended on the resources provided by individual plants. At large scales (radii > 25 m around focal plants), high sugar density decreased per‐plant visitation rates, i.e. plants competed for animal pollinators. At small scales (radii < 5 m around focal plants), we observed either competition or facilitation for pollinators between plants, depending on the sugar amount offered by individual focal plants. In plants with copious sugar, per‐plant visitation rates increased with increasing local sugar density, but visitation rates decreased in plants with little sugar. Our study underlines the importance of scale‐dependent responses of pollinators to floral resources and reveals that pollinators' responses depend on the interplay between individual floral resources and local resource neighbourhood.